Postischemic brain infiltration of leukocyte subpopulations differs among murine permanent and transient focal cerebral ischemia models - Zhou, Wei; Liesz, Arthur; Lahrmann, Bernd; Valous, Nektarios A.; Grabe, Niels; Veltkamp, Roland (Brain pathology, 2013)
Cellular and humoral inflammations play important roles in ischemic brain injury. The effectiveness of immunomodulatory therapies may critically depend on the chosen experimental model. Our purpose was to compare the post-ischemic neuroinflammation among murine permanent and transient middle cerebral artery occlusion (MCAO) models. Permanent MCAO was induced by transtemporal electrocoagulation and 30 minutes or 90 minutes transient MCAO was induced by intraluminal filament in C57BL/6 mice. Infiltration of leukocyte subpopulations was quantified by immunohistochemistry and fluorescence-activated cell sorting. Cerebral cytokine and adhesion molecule expression was measured by real-time polymerase chain reaction (RT-PCR). Neutrophil infiltration was noted at 24 h after transient MCAO, but did not further increase until 5 days in the permanent MCAO model. Few T cells were observed in both MCAO models at 24 h, but permanent MCAO demonstrated much more infiltrating T cells at 5 days. Pronounced microglial activation was evident at 24 h and 5 days after permanent but not after transient MCAO. The number of invading NK cells and expression of MHCII on CD11b+ cells did not differ among the three groups. Five days after MCAO, the expression of IL-1, TNF-α and IFN-γ and of the adhesion molecules ICAM-1 and VCAM-1 was significantly higher in the permanent than in the transient MCAO groups. Cellular and humoral inflammation differs substantially among commonly used MCAO models. Neuroinflammation is more pronounced after permanent electrocoagulatory MCAO compared with 30 minutes and 90 minutes filament-MCAO.